KARAKTERISTIK IBU BERDASARKAN PERBAIKAN GIZI BALITA STUNTING DI PUSKESMAS MANGKUPALAS SAMARINDA - Abdillah, Hazimah Qisthina; Bakhtiar, Rahmat; Zubaidah, Mona (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
Stunting is a chronic malnutrition problem that is caused by a lack of nutrition in a long time due to food that is not following nutritional needs and minerals and reduced diversity of food and animal protein sources. Maternal factors and poor parenting also play a role, especially in the practice of feeding causes children to become stunted if the mother does not provide adequate and proper nutrition. The purpose of this study was to determine the description of maternal characteristics based on nutrition improvement in stunting toddlers in Samarinda Mangkupalas Health Center. This research is a descriptive observational study. The sample of this study was mothers of stunting toddlers in the Mangkupalas Community Health Center area, by the characteristics of the sample determined by the researchers, which were taken by purposive sampling technique. The data used are primary data obtained from the results of filling out the questionnaire, taken in September - October 2019 at the Mangkupalas Health Center in Samarinda. The number of samples obtained was 30 respondents. The results generally show that the age of stunting mothers is the most at the age of <35 years (76.7%), the last high school education (46.7%), and not working (80%).